Fear of discovery as a deterrent to undocumented Latinx immigrants' reporting of crimes and the effects of political rhetoric. (15th February 2021) - Rodriguez, Robert M.; Torres, Jesus R.; Sun, Jennifer; Anderson, Erik
Abstract: Objectives: Comparing undocumented Latinx immigrants (UDLI), Latinx citizens/residents (LCR), and non‐Latinx citizens/residents (NLCR), we sought to assess rates of crime victimization, fear of reporting crimes, causes of this fear, and whether political rhetoric from the U.S. President had changed the reporting of crimes. Methods: From October 2018 to February 2020, we conducted this in‐person survey study, enrolling similar numbers of UDLI, LCR, and NLCR patients at two urban county hospital emergency departments (EDs) in San Francisco and Oakland, California. Our primary outcomes were responses to key survey questions regarding crime victimization, fear of reporting crimes and the effects of anti‐immigrant rhetoric on reporting crimes. Results: Of 667 patients approached, 531 (80%) participated and six participants were excluded: 165 (31.3%) were UDLI, 183 (34.7%) were LCR, and 177 (33.6%) were NLCR. Similar percentages of UDLI (34%), LCR (32%), and NLCR (39%) knew of someone (themselves, friends, or family) who was a victim of a crime. Similar percentages of UDLI (41%), LCR (46%), and NLCR (41%) stated that these victims were afraid to report this crime to the police. The primary reason for this fear in UDLI was fear of discovery and deportation (30%). Similar percentages of UDLI (63%), LCR (58%), and NLCR (46%) ultimately reported the crime to the police. Most (85%) respondents had heard the U.S. President's statements about measures against immigrants; 54% reported that they believe that because of these statements, people are more afraid to report a crime to the police. Conclusions: Fear of reporting crimes is common in ED patients. The most common fear in UDLI is fear of discovery and deportation. Political rhetoric against immigrants contributes to this fear.